Posterior Monteggia Fracture–Dislocation in a 70-Year-Old Woman After a Low-Energy Bicycle Fall: Successful Management in a Resource-Limited Setting: A Rare Case Report - Danika Andri; Fauzan Andi Muhammad Ihsan; Putra Hisyam Hartaman; Muhammad Aan Tri Lutfi; Saribudaya Agus (The International Journal of Medical Science and Health Research, 2025)
A Monteggia fracture occurs when the proximal ulna fractures and the proximal radioulnar joint (PRUJ) is disrupted. This type of fracture is uncommon in adults, making up approximately 1% to 5% of all elbow fractures. This fracture's aetiology follows a bimodal pattern: low-energy trauma, such as falls on the ground, is typically the cause in older women, whereas high-energy trauma, like falls from heights and sports injuries, is usually the cause in young men. A 70-year-old woman came to the hospital emergency room complaining of pain in her left elbow. The patient experienced pain 30 minutes after falling off their bicycle. The patient fell sideways, and their left elbow bore the weight during the fall. The patient is unable to move their elbow. The fingers can still be moved. On physical examination, the following findings were observed: deformity, PRUJ dislocation, tenderness to palpation, crepitus, and limited range of motion due to pain. After that, an X-ray of the elbow was taken in the AP-lateral view, which revealed a comminuted Monteggia fracture Bado type II on the left side. The PRUJ joint was openly repositioned during the surgery. Following that, the comminuted Monteggia fracture was internally fixed. Since a locking plate was not available, we used a modified (bent plate) small bone plate type D with 12 holes instead of the plate and screw that we used for ORIF. After that, the plate was attached using seven cortical screws. During the elbow joint ROM test, unfortunately the PRUJ dislocation was not stable. Furthermore, it was decided to perform pinning with a K-wire from the capitellum toward the head of the radius. After that, one cortical screw was inserted on the medial side to stabilize the fracture fragments, and a hydroxyapatite bone graft was added to the comminuted fracture area. Two days after the operation, the patient is allowed to go home. Our patient is a elderly woman who experienced a Monteggia fracture, Bado classification type II occurs due to low energy. In the elderly, this mechanisms are a common cause. In this case, it is recommended to use a locking compression plate (LCP), but due to limited resources, we used a modified (bending plate) small bone plate type D. This can provide an alternative and also a practical solution in the management of Monteggia-Bado classification type 2 fractures at the healthcare level with limited resources for modern plates.